Insights into collective cell behaviour from populations of coupled chemical oscillators. Issue 31 (21st August 2015) - Taylor, Annette F.; Tinsley, Mark R.; Showalter, Kenneth
<x xml:space="preserve">Abstract</x> Biological systems such as yeast show coordinated activity driven by chemical communication between cells. Experiments with coupled chemical oscillators can provide insights into the collective behaviour.